2022
DOI: 10.1111/acer.14789
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use, behavioral and mental health help‐seeking, and treatment satisfaction among sexual minority women

Abstract: Background Sexual minority women (SMW) report higher rates of heavy episodic drinking (HED) and adverse alcohol‐related outcomes, including poor mental health, than heterosexual women. These disparities indicate a greater need for behavioral and mental health treatment for SMW. This study examined associations among alcohol outcomes, behavioral and mental health help‐seeking, and treatment satisfaction among SMW by age, sexual identity, race/ethnicity, and income. Methods Participants included a community samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 80 publications
0
0
1
Order By: Relevance
“…We found that Black women had higher odds of harmful drinking, after adjusting for covariates. Previous studies have shown a higher risk of alcohol and other drug use among sexual minority women of color compared to that among white sexual minority women [14,46]. Although we did not find any evidence for effect modification between sexual orientation and harmful drinking by race/ethnicity, our research was likely limited by the small subgroup of sexual minority women of color.…”
Section: Discussioncontrasting
confidence: 90%
“…We found that Black women had higher odds of harmful drinking, after adjusting for covariates. Previous studies have shown a higher risk of alcohol and other drug use among sexual minority women of color compared to that among white sexual minority women [14,46]. Although we did not find any evidence for effect modification between sexual orientation and harmful drinking by race/ethnicity, our research was likely limited by the small subgroup of sexual minority women of color.…”
Section: Discussioncontrasting
confidence: 90%